Formação planetária em sistemas binários - Barbosa, Gerson de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The number of confirmed exoplanets exceeds three thousand. And it is also known that more than half of these exoplanets are in multiple star systems. With this, many questions concerning the formation processes for which these planets were submitted generate many discussions in scientists today. Although the solar system is our backyard of orbital dynamics research, theories about its process of formation are still being discussed and studied. A study of the process of formation in binary systems can help us to improve and build a broad theory of formation, and even contribute to theories of the formation of the solar system. Questions about the possible existence of life in these systems further increase the need for a better understanding of the formation processes. So, the objective of this work is to test new N-body simulation software adapted from the Mercury package, and with it to study the possible formation of terrestrial planets in the habitable zone of binary systems with P-type orbits. In order to test the adapted computational package, we have reproduced some numerical simulations of Elisa V. Quintana 2004, in order to compare the results, and thus first check the reliability of our software. After the completed integrations, we can statistically check that our results show good reliability. The second step of the work was to perform some simulations using data from the binary systems Kepler 16, Kepler 34, Kepler 35 and Kepler 38. After the simulations, we noticed the existence of stability in the regions of habitable zone and the possibility of planetary formation

O número de exoplanetas confirmados hoje passa de três mil. E sabe-se também que mais da metade desses exoplanetas estão em sistemas estelares múltiplos. Com isso, muitas questões referentes aos processos de formação pelos quais esses planetas foram submetidos, geram muitas discussões nos cientistas atualmente. Apesar de o sistema solar ser nosso quintal de pesquisas de dinâmica orbital, teorias sobre seu processo de formação ainda está sendo discutido e estudado. Portando, um estudo ao processo de formação em sistemas binários, pode nos ajudar a entender melhor e a construir uma ampla teoria de formação, conseguindo contribuir inclusive para teorias da formação do sistema solar. Questões referentes à possível existência de vida nesses sistemas aumentam ainda mais a necessidade de um melhor entendimento dos processos de formação. Contudo, o objetivo desse trabalho é testar um novo software de simulação de N-corpos adaptado do pacote Mercury, e com ele estudar a possível formação de planetas terrestres na zona habitável de sistemas binários com órbitas P-type. Para testar o pacote computacional adaptado, reproduzimos algumas simulações numéricas de Elisa V. Quintana 2004, na intenção de comparar os resultados, e assim primeiramente checar a confiabilidade do nosso software. Após as integrações concluídas, podemos checar estatisticamente que nossos resultados apresentam uma boa confiabilidade. Assim com o pacote testado, a segunda etapa do trabalho foi realizar algumas simulações, utilizando dados dos sistemas binários Kepler 16, Kepler 34, Kepler 35 e Kepler 38. Após as simulações, percebemos a existência de estabilidade nas regiões de zona habitável e a possibilidade de formação planetária
Keywords: Exoplanetas; Planetas; Sistema binário (Matemática); Sistema solar; Extrasolar planets